Pathogenic bacteria present on scrap meat loaf sold in Blumentritt and Quiapo Public Market - Marc Dave S. Angeles. 4 0 16; 5 (2007)
u
Thesis:(B.S. Biology)-Pamantasan ng Lungsod ng Maynila, 2007.
Keywords: 2 -- 0; 6; 20; 20; 2